2017
DOI: 10.1016/j.physleta.2017.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Quantum periodicity in the critical current of superconducting rings with asymmetric link-up of current leads

Abstract: We use superconducting rings with asymmetric link-up of current leads for experimental investigation of winding number change at magnetic field corresponding to the half of the flux quantum inside the ring. According to the conventional theory, the critical current of such rings should change by jump due to this change. Experimental data obtained at measurements of aluminum rings agree with theoretical prediction in magnetic flux region close to integer numbers of the flux quantum and disagree in the region cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
0
10
0
3
Order By: Relevance
“…The two state n = n ′ and n = n ′ + 1 have the same value of the kinetic energy in (7) E k = (nΦ 0 − Φ) 2 /2L k = Φ 2 0 /8L k at Φ = (n ′ + 0.5)Φ 0 . According to the universally recognized explanation [33] the quantum periodicity in the transition temperature [20], the ring resistance [24,27], the magnetic susceptibility [23], the dc voltage [21,22,28,29] and the critical current [25,26,30] are observed due to the change of the quantum number n with the magnetic flux at Φ = (n ′ + 0.5)Φ 0 .…”
Section: Changes Of the Quantum Number Of Superconducting Ringsmentioning
confidence: 99%
“…The two state n = n ′ and n = n ′ + 1 have the same value of the kinetic energy in (7) E k = (nΦ 0 − Φ) 2 /2L k = Φ 2 0 /8L k at Φ = (n ′ + 0.5)Φ 0 . According to the universally recognized explanation [33] the quantum periodicity in the transition temperature [20], the ring resistance [24,27], the magnetic susceptibility [23], the dc voltage [21,22,28,29] and the critical current [25,26,30] are observed due to the change of the quantum number n with the magnetic flux at Φ = (n ′ + 0.5)Φ 0 .…”
Section: Changes Of the Quantum Number Of Superconducting Ringsmentioning
confidence: 99%
“…The change of the average value of the critical current and the voltage (11) in a small interval of the magnetic flux δΦ was proposed to be used to create a magnetometer with high sensitivity and easy to manufacture [41]. But the first measurements of aluminium rings with asymmetric link-up of current leads revealed that a smooth change of the critical current is observed near Φ = (n ′ + 0.5)Φ 0 instead of the jump [42], contrary to the theoretical prediction. In contrast to these experimental results, the observations of the voltage jumps [25] guarantees the possibility to make a sensitive magnetometer based on the DDCI.…”
Section: Discussionmentioning
confidence: 99%
“…The jump of the critical current must be observed at measurements of asymmetric rings. But this jump is not observed [9,21] for some strange reason. …”
Section: Strong Discreteness Of the Energy Spectrum Of Continuous Supmentioning
confidence: 91%
“…A simple magnetometer based on the latter prediction was proposed in [20]. But measurements of aluminium ring with asymmetric link-up of current leads have revealed that a smooth change of its critical current is observed at Φ ≈ (n + 0.5)Φ 0 instead of the jump which must be observed due to the change of the quantum number from n to n+1 [21]. Our observations of the voltage jumps up to V max −V min ≈ 20 µV , Fig.3, and higher mean that the derivative (∂V /∂Φ e ) I can reach high values when the voltage V average in the time Θ ≫ 1/f changes from…”
mentioning
confidence: 99%